Collection of Value Added Tax in Kosovo and Its Effect on Economic Growth - Shala, Teki (European Journal of Economics and Business Studies, 2017)
The revenue collected from the value added tax constitutes the main income of the Kosovo government. For this reason, this research has a great importance in the formulation of effective policies in Kosovo that will subsequently improve the efficiency of tax collection of Value Added and growing fiscal and budgetary stability. This research it will have a descriptive analysis of the trends of VAT collection in Kosovo from 2005- 2015 years using different analytical techniques to examine trends and data structure over the years. We have used two types of analysis; One is the descriptive analysis of trends and the other is the contrast of the descriptive analysis of trends that is the econometric technique used to analyze the VAT effect on economic growth in Kosovo. The source of data for this study is secondary through the Annual Financial Report of the Ministry of Finance of Kosovo and the IMF. In order to analyze the data generated for the study, the statistical tool utilized is OLS technique (multiple regression). One of the key findings in the collection of VAT has been its dependence on the border. Revenue collection is among the most pressing problems and such situation does not guarantee a country's budgetary stability. Also, based on the findings we noted that the VAT share of the gathering in gross domestic product of the Interior of the country has been low compared to other countries in Europe developing, reflecting a low level of economic development. Also from econometric analysis is confirmed that the regression coefficient shows that we have a VAT impact on GDP in Kosovo, because the level of significance is .000, or includes the rate of 1 percent. Also, the correlation between VAT and GDP shows a strong positive relationship, or statistically interpreted with the increase of VAT, will increase the GDP of Kosovo, these two elements conclude that VAT has a significant impact on economic growth in Kosovo. Furthermore, this research highlight some key issues that policy makers should consider dealing with the collection and effective use of revenue collected from VAT, to improve growth.
Keywords: Domestic Product, Tax, Economic Growth, Revenue, etc.